Entrepreneurial Instincts of Nurses and Midwives in Ghana - Ofei. A,M.A.; Owusu-Asiamah. J.; Barnes. T.; Annan. E. (Nursing Open, 2025)
Background: In recent years, the popularity of entrepreneurship among nurses and midwives has increased. People in the nurs ing and midwifery professions have reaped numerous benefits from this endeavour. However, little is known about the reasons why nurses and midwives decide to become business owners. The aim of the study was to explore the motivation for entrepre neurial instincts among nurses and midwives in Ghana. Methodology: This qualitative study snowball- sampled nurses and midwives in the Greater Accra Region who have estab lished their health- related businesses. The participants consisted of eleven participants based on theoretical saturation. Using an interview guide, researchers gathered in- depth data on the discussed phenomenon and then analysed the data using thematic analysis. Results: Five themes were identified from analysis of data, and they are frustration at the former workplace, the desire to own a business, preserving family legacy, the necessity for extra income, and engaging in something during retirement. Conclusion: Nurses and midwives gain experience through their work as professionals, which motivates them to become en trepreneurs. In addition to these experiences, other factors play an important role in the entrepreneurial ambitions of nurses and midwives. Patient or Public Contribution: We are grateful to all nurses and midwives for their help during the study.
Research Article
Keywords: entrepreneurship; midwives; motivation